ISSUES OF INVESTIGATION OF CRIMES IN THE FIELD OF MEDICAL TRANSPLANTOLOGY - Topildieva Dilrabo Mirshakhidovna (International Journal of Business, Law and Political Science, 2024)
The fourth generation rights, which include somatic rights, evoke several controversies. One of the rights is considered human right to organ and tissue transplantation. Issues of investigation of crimes in this sphere are discussed in the article. The author notes that there are a number of problems, including moral and legal ones, in the investigation of these acts. It is necessary to develop high technologies that will improve the level of medical knowledge of crime investigators, as well as, introduce a system of independent examination to solve most of the legal and forensic problems; otherwise, there is a high probability of abuse, both by doctors and by criminal groups.